2023
DOI: 10.1109/tem.2021.3066153
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Factors Influencing Big Data Technology Acceptance

Abstract: Big Data has received great attention in academic literature and industry papers. Most of the experiments and studies focused on publishing results of big data technologies development, machine learning algorithms, and data analytics. To the best of our knowledge, there is not yet any comprehensive empirical study in the academic literature on big data technology acceptance. The statistical results of this model provide a compelling explanation of the relationships among the antecedent variables and the depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 115 publications
(153 reference statements)
1
18
0
Order By: Relevance
“…The analysis also supports the use of IoT devices for improving SCP. The result of earlier studies [44], [71], [75], [88] in different sectors of SC demonstrated the benefits of using IoT devices for improving SCP also supports the result of this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The analysis also supports the use of IoT devices for improving SCP. The result of earlier studies [44], [71], [75], [88] in different sectors of SC demonstrated the benefits of using IoT devices for improving SCP also supports the result of this study.…”
Section: Discussionsupporting
confidence: 89%
“…IoT can be used to track behavioral change and helps in maintaining data of vaccinated person. IoT-enabled transportation system would help anyone to trace the origin [71], and manufacturing process of vaccine with all the necessary condition of its transportation and storage. These facilities with effective information coordination enabled by IoT might change the behavior of people toward vaccination.…”
Section: Impact Of Supply Demand and Social Behavior On Iot And Scpmentioning
confidence: 99%
“…Moreover, these BDAC dimensions are inextricably intertwined and mutually supportive [7] and when combined effectively is a rare and imperfectly imitable resource [14]. For example, building BDA technological capabilities requires managers and staff to update their technical and analytical skills or hire new talent with the requisite skills [52]. This was a huge challenge for many firms [35], [50], [53].…”
Section: B Bda Capabilitiesmentioning
confidence: 99%
“…Modern slavery and CSR: The ARM industry is one of the most labor-intensive industries in the world. It is also the sector in which modern slavery 4 and CSR problems deserve close examinations. One key challenge behind the proper management in having an ethical apparel supply chain is the lack of transparency.…”
Section: Future Research Agenda and Conclusionmentioning
confidence: 99%
“…1) the proper use of data analytics tools, especially social media analytics [6], for ARM; 2) the technology acceptance models for data analytics by apparel companies [4]; 3) the project management schemes to effectively implement new technologies while facing business downturn in the postpandemic era. Industry 5.0: The AMR industry has actively engaged in many intelligent production and operations systems with various popular technologies.…”
Section: Future Research Agenda and Conclusionmentioning
confidence: 99%